Impact of stress and parenting on respiratory sinus arrythmia trajectories in early adolescence. Issue 6 (22nd July 2021) - Lisitsa, Ellie; Bolden, China R.; Johnson, Benjamin D.; Mezulis, Amy H.
Abstract: The effects of stress and parenting on 1‐year trajectories of physiological emotion regulation capacity among adolescents were examined. Consistent with the vulnerability‐stress and allostatic load models, stress (chronic family and marital) was hypothesized to be associated with less favorable trajectories of basal respiratory sinus arrhythmia (RSA) over 1 year. This relationship was further hypothesized to be moderated by parenting practices (warmth, neglect, and rejection) and adolescent sex. Participants included 150 adolescents (51.3% female), 11–15 years of age ( M = 13.04, SD = 0.89). Basal RSA and stress were assessed four times across 1 year. Results indicated a significant decrease in RSA over the course of 1 year (β = −0.15, p = .010). Warm parenting style was associated with lower RSA in environments of low marital stress and was also related with higher RSA in environments of high marital stress (β = 0.86, p = .021). Rejecting parenting styles were associated with higher RSA in environments of low family stress and lower RSA in environments of high family stress (β = −0.60, p = .014). These findings may be explained by the Yerkes–Dodson law of optimal stress, suggesting that sufficient environmental challenge is needed to catalyze regulatory development.